Improved treatment of dark matter capture in neutron stars II: leptonic targets. Issue 3 (26th March 2021) - Bell, Nicole F.; Busoni, Giorgio; Robles, Sandra; Virgato, Michael
Abstract: Neutron stars harbour matter under extreme conditions, providing a unique testing ground for fundamental interactions. We recently developed an improved treatment of dark matter (DM) capture in neutron stars that properly incorporates many of the important physical effects, and outlined useful analytic approximations that are valid when the scattering amplitude is independent of the centre of mass energy. We now extend that analysis to all interaction types. We also discuss the effect of going beyond the zero-temperature approximation, which provides a boost to the capture rate of low mass dark matter, and give approximations for the dark matter up-scattering rate and evaporation mass. We apply these results to scattering of dark matter from leptonic targets, for which a correct relativistic description is essential. We find that the potential neutron star sensitivity to DM-lepton scattering cross sections greatly exceeds electron-recoil experiments, particularly in the sub-GeV regime, with a sensitivity to sub-MeV DM well beyond the reach of future terrestrial experiments.